Pelaksanaan Protokol Kesehatan Corona Virus Disease 2019 Oleh Masyarakat di Kabupaten Minahasa Tenggara - Oksfriani Jufri Sumampouw (Universitas Sam Ratulangi, 2020)
Background: The government has set various policies in order to control the spread of Corona Virus Disease 2019 (Covid-19). However, these efforts have not implemented optimally. The purpose of this study was to describe the health protocol implementation of the Covid-19 to prevention of Covid-19 in Southeast Minahasa Regency. Methode: This research was conducted in Southeast Minahasa Regency in August 2020. The subjects in this study were 210 family heads who met the inclusion criteria. The research variable is the implementation of health protocols in an effort to prevent Covid-19. The research data were analyzed by univariate. Presentation of data is made in table and narrative form. Result: This study showed that people who have the habit of washing hands are 87.9% (high category), using masks by 86.1% (high category) and keeping their distance by 77.5% (high category). Conclusion: The conclusion of this study is that the community has carried out the health protocol well. However, it is necessary to carry out continuous and massive socialization and monitoring efforts in order to reduce the rate of increase in Covid 19.